Relative Efficiency by Farm Size and the Green Revolution in Pakistan (The Pakistan Development Review, 1980)
Using the "unit output price" profit function, the study analyses the relative efficiency of (a) old versus new seeds, and (b) large versus small farms in the production of new varieties of wheat and rice in the Indus Basin of Pakistan. It is found that whereas farm .size has no effect on efficiency, high-yielding seeds are more efficient than seeds of old varieties. The study also finds that labour demand elasticities with respect to both land and capital are rather low.